Video conferencing over IP configure, secure, and troubleshoot - Gough, Michael 1963- (Syngress, 2006)
Annotation
Includes bibliographical references and index
Keywords: COMPUTERS / Networking / Vendor Specific; COMPUTERS / Data Transmission Systems / General; Internet videoconferencing; Videoconferencing